Upaya Meningkatkan Prestasi Belajar Matematika dengan Alat Peraga pada Siswa Kelas III SD Negeri 3 Kemiling Permai Bandar Lampung - Ngatiyem, Ngatiyem (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2015)
The research objective to be achieved are: to determine the increase mathematics achievement in aspects of learning fractions by using props in the second grade students of SD Negeri 3 Kemiling Bandar Lampung Regency Kota Permai academic year 2014/2015. Forms of research in this thesis using the draft action research. While the population in the study were used in this study was grade II SD Negeri 3 Kemiling Permai academic year 2014/2015. with a total population of some 32 students. As for the sample in this study there are entire populations in grade II SD Negeri 3 Kemiling Permai the number of 32 students. In collecting the data, the methods used are basic methods which include test methods, observation and documentation. Test method is used to get the students learning achievement after getting instruction cycle I and cycle II., Observational methods used to determine the condition of the school, the condition of the current students to get good teaching in cycle I, and II, methods of documentation used to determine the name of research respondents. To test the validity of the data used triangulation of data, and triangulation methods. In the process of analysis, there are three components that must be realized by the researchers. The three components are: 1) Data reduction; 2) data presentation, 3) conclusion or verification Based on the results and discussion can be seen that. 1. The average value of mathematics learning achievement of third grade students in the first cycle by 67, the second cycle of 76 so there is a rise in value - average of the first cycle to the second cycle 2. Percentage of mastery learning students in the first cycle shows the figure of 60.97% (25 students completed the study of all participants 41 students), in the second cycle of 97.6% (students completed the study of all the participants of 32 students). Thus there is an increasing mastery learning students from the first cycle to the second cycle. Based on the above, it can be made a conclusion as follows: Through the props can improve mathematics achievement in grade II SD country 3 Kemiling Permai academic year 2014/2015.